Re-imagining religion and belief 21st century policy and practice - Baker, Christopher 1961-; Crisp, Beth ca. 20./21. Jh; Dinham, Adam 1974- (Policy Press, 2018)
With growing diversity of religion and belief in every sector comes the potential for new dialogues across previously impermeable policy and disciplinary silos. This volume critically challenges policy makers to re-imagine religion and belief as an integral part of public life that contains resources, practices, forms of knowledge and experience
Title from publisher's bibliographic system (viewed on 07 Apr 2022)
Keywords: .Religion and sociology; Social policy